2022
DOI: 10.3390/polym14030453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Oxide on the Low-Temperature Crack Resistance of Polyurethane–SBS-Modified Asphalt and Asphalt Mixtures

Abstract: In this study, the novel nanomaterial graphene oxide (GO) was added as a modifier to polyurethane–styrene-butadiene-styrene (SBS)-modified asphalt, and a graphene oxide/polyurethane/SBS composite-modified asphalt mix was prepared. The effect of the graphene oxide material on the low-temperature crack resistance of the asphalt and mixes was investigated by bending beam rheometer (BBR) tests, beamlet bending tests at different low temperatures, and characterization by scanning electron microscopy for its microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…GO was a two-dimensional and lamellar nanometer carbon material with a high specific surface area and large functional groups (Lin et al, 2019;Sali et al, 2019;Hu et al, 2021). There were many polar functional groups on the two-dimensional surface of GO, such as hydroxyl, carbonyl, carboxyl, and epoxy functional groups (Joshi et al, 2021;Li et al, 2022).…”
Section: Interaction Of Go and Wevamentioning
confidence: 99%
See 1 more Smart Citation
“…GO was a two-dimensional and lamellar nanometer carbon material with a high specific surface area and large functional groups (Lin et al, 2019;Sali et al, 2019;Hu et al, 2021). There were many polar functional groups on the two-dimensional surface of GO, such as hydroxyl, carbonyl, carboxyl, and epoxy functional groups (Joshi et al, 2021;Li et al, 2022).…”
Section: Interaction Of Go and Wevamentioning
confidence: 99%
“…The WEVA particles suspended in the modified asphalt system became smaller and more even, along with the increased content of GO in Figure 2. As there is no improvement in GO-modified asphalt, the progress of composite asphalt modified by GO and WEVA comes from the effect of GO on WEVA particles (Li et al, 2022). Based on the mentioned changes in physical properties of modified asphalt, the respective characteristics of modifier, and their effect on the modification, we conducted the schematic (Figure 5) to clarify the interaction of GO and WEVA in the asphalt modification.…”
Section: Interaction Of Go and Wevamentioning
confidence: 99%
“…Jang et al have demonstrated that GO has the potential to enhance the thermal, mechanical, conductive, and rheological properties of poly­(methyl methacrylate). GO is also anticipated to yield significant improvements in asphalt binders, enhancing their performance and addressing issues such as rutting, , fatigue, , and thermal cracking. , Additionally, some researchers have proposed that GO could serve as an antiaging material. For example, Adnan et al conducted an analysis of the influence of GO on the properties of asphalt binder.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a few studies have reported on the enhancement effect of GO on the performance of SBS-MA. As a reinforcing agent, GO can remarkably improve the aging resistance of asphalt mixtures, owing to its ability to reduce the degradation of SBS modifiers and change the crosslinked composite structure of asphalt [ 23 , 24 ]. Favourable high-temperature rheological properties were also obtained for the asphalt binder by doping SBS with GO to form a composite modifier [ 25 ].…”
Section: Introductionmentioning
confidence: 99%